DISKURSUS KEPEMIMPINAN KONTEMPORER: POLA KOMUNIKASI POLITIK DAN STRATEGI ADAPTASI PEMIMPIN MUDA DALAM LANSKAP DEMOKRASI DIGITAL - ZA, Safrizal; Alqarni, Wais; Zuhri, M.; Agustina, Soraya; Alysha, Putri (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This study analyzes the political communication patterns and adaptation strategies of young leaders in the landscape of digital democracy, focusing on Gibran Rakabuming Raka as the primary case study. Using a qualitative literature review approach, the research explores how young leaders utilize social media as an effective communication tool to build self-image, public interaction, and political agenda dissemination. The findings reveal that Gibran's communication style represents a shift from traditional hierarchical approaches to participatory strategies through digital platforms such as Instagram, Twitter, and TikTok. Adaptation strategies include responsiveness to public criticism and the ability to transform negative narratives into effective communication opportunities. The study also highlights that challenges, such as symbolic attacks and delegitimization in the digital public sphere, can be addressed through innovative and humorous communication approaches. These findings emphasize that young leaders have significant potential to drive transformation in political communication in the digital era, prioritizing participation, transparency, and rapid adaptation to technological dynamics.